O deficiente visual e o ensino fundamental: um estudo etnográfico sob a perspectiva da pesquisa transformativa do consumidor - Coelho, Pedro Felipe da Costa (2016)
The purpose of this research was to understand the consumer behavior of visually impaired people in consuming educational services during elementary school, aiming to develop initiatives to mitigate its vulnerability as consumer. The ethnographic research, developed in a NGO, which is engaged in the education of students with visual impairment in João Pessoa /PB, was preceded by a review of literature about the Transformative Consumer Research, the Consumer Vulnerability and the performance of visually impaired people as consumers with emphasis on the consumption of educational services. The data were collected through 17 narrative interviews with elementary school students supported by this institution, six in-depth interviews with managers and teachers of the NGO Lar, five interviews with relatives of these students, and seven months of participant observation inside the institution. The results of the research indicate that the schoolmates, teachers, school managers and NGOs that work with visually impaired people interfere directly in the consumption behavior of the subjects, being able to contribute or inhibit the subjective well-being of the students. In addition, the powerlessness before unfair taxes, the lack of open positions in public or private schools and the lack of adequate teaching materials are characteristics of the investigated context that accentuate the vulnerability state of respondents. Starting the debate in Marketing of educational services in elementary school and developing this research on the fundamentals of Transformative Consumer Research can be considered theoretical contributions of this study, which also has practical contributions to civil society organizations from Joao Pessoa.